Once and for all : [book club bag] a novel - Dessen, Sarah (Viking, 2017)
Louna's years working at her mother's wedding planning business--as well as the tragic end of her first love--have shaped her cynical views on romance, but the arrival of serial-dater Ambrose may start to change Louna's mind and give her a second chance at love.